2016
DOI: 10.7717/peerj.2421
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive personality profiles of fibromyalgia and chronic fatigue syndrome patients

Abstract: ObjectiveThe current study is an innovative exploratory investigation, aiming at identifying differences in personality profiles within Fibromyalgia Syndrome (FMS) and Chronic Fatigue Syndrome (CFS) patients.MethodIn total, 344 participants (309 female, 35 male) reported suffering from FMS and/or CFS and consented to participate in the study. Participants were recruited at an Israeli FM/CFS patient meeting held in May 2013, and through an announcement posted on several social networks. Participants were asked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 46 publications
2
28
1
Order By: Relevance
“…34 In another study performed in Israel, 30% of FM patients were found to have type D personality. 35 In the present study, 33% of FM patients were found to have Type D personality; this rate was significantly higher than that of healthy controls (12%). In previous studies, the frequency of type D personality construct in Turkey was described as follows: 27.7% in hemodialysis patients 31 and 56.8% in patients with multiple sclerosis.…”
Section: Discussioncontrasting
confidence: 46%
“…34 In another study performed in Israel, 30% of FM patients were found to have type D personality. 35 In the present study, 33% of FM patients were found to have Type D personality; this rate was significantly higher than that of healthy controls (12%). In previous studies, the frequency of type D personality construct in Turkey was described as follows: 27.7% in hemodialysis patients 31 and 56.8% in patients with multiple sclerosis.…”
Section: Discussioncontrasting
confidence: 46%
“…Regarding Definition and Diagnostic Criteria of Fibromyalgia Twenty studies [ 2 , 3 , 5 , 6 , 19 - 26 , 28 , 29 , 33 - 41 ] defined fibromyalgia as a syndrome characterized by chronic widespread pain and sensitivity to digital palpation and only one study referred to fibromyalgia as a rheumatic disease [ 35 ]. Nineteen of these studies [ 2 , 3 , 5 , 6 , 19 , 23 , 25 , 26 , 28 , 29 , 33 - 41 ] add to this basic definition the presence of fatigue, sleep disorders, cognitive impairment and emotional distress. Furthermore, 5 studies [ 5 , 19 , 29 , 35 , 36 ] highlighted the presence of sensitivity to tender points (11/18) as described by ACR criteria for FM diagnosis in 1990 [ 21 ] while only two studies referred explicitly to the new ACR criteria [ 13 ] for its definition and diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…In three studies [ 35 , 36 , 39 ], participants were selected from previously used databases. Ten studies clearly used the ACR criteria to select participants with FM; in one study the participants were described as people who meet the ACR criteria, without other specifications [ 37 ], 7 referring to ACR criteria of 1990 [ 2 , 3 , 6 , 23 , 25 , 29 , 39 ] and only 3 used the 2010 criteria [ 28 , 38 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations